Do primary and specialized care physicians know and use coordination mechanisms? - Lívia dos Santos Mendes; Patty Fidelis de Almeida (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVES: To analyze if primary and specialized care physicians know and use care coordination mechanisms between healthcare levels. METHODS: Cross-sectional survey study, with the application of the COORDENA-BR instrument to primary and specialized care physicians in a public heathcare network, medium-sized municipality, from June to October 2019. The questionnaire addresses knowledge, frequency of sending and receiving, purpose, characteristics and difficulties in using feedback or mutual adaptation and standardization mechanisms to promote coordination of care service between healthcare levels. RESULTS: Feedback instruments such as referral and reply letters, hospital discharge report and WhatsApp are widely known by professionals of both levels, without significant differences. Clinical sessions and protocols are not well-known, especially in specialized care, which supposes a low usage of standardization mechanisms to a better coordination between the healthcare levels. Despite being well-known and easy, traditional feedback instruments such as referral and reply letters are not widely used. Fewer physicians knew the protocols, mainly in specialized care. They pointed difficulties in their application, such as insufficient exams and unavailable supplies in the healthcare network. Clinical sessions were unknown and registered low participation frequency. Care overload, low institutionalization and time constraints were barriers identified for the incorporation of care coordination mechanisms in the work process in primary and specialized care, in addition to those related to the provision of health services in the network. CONCLUSION: We conclude the fragmentation of the system and care can be faced in the complementarity of measures that make it possible to know the mechanisms, develop professional skills, institutionalize and promote organizational conditions for the effective use of coordination mechanisms throughout the healthcare network.